PROJETO KARST: WATER BALANCE AND ISOTOPE INVESTIGATIONS IN THE COMPARTMENT KARST AQUIFER OF COLOMBO-FERVIDA (CURITIBA/PR) - Harum, T.; Leditzky, H. P.; Reinsdorff, S.; Saccon, P.; Zojer, H.; Lisboa, A. A.; Vaine, J. L.; Rosa Filho, E. F. da; Giusti, D. A.; Monastier, M. S.; Ribas, A. (Águas Subterrâneas, 2000)
The paper gives an overview about the first results of an international co-operation project carried out in the karst aquifer of Colombo-Fervida 20 km N of Curitiba (Paraná). The aquifer is separated into compartments due to NW-SE-striking volcanic dikes which cut through a sequence of folded phyllites and carbonate rocks. The carbonate rocks are karstified and therefore represent an important aquifer which is partly drained by springs, but also exfiltrates to small creeks. The dikes can be considered as impermeable layers separating the aquifer to isolated compartments. Most of the springs are located at the contact of the aquifer to dikes. Combined investigations on geology, tectonics, catchment and isotope hydrology allowed to develop a conceptual model of groundwater recharge and transit times. The relatively high mean transit times (18-36 y) confirm the huge storage in the unsaturated zone of the weathered layer with thickness up to 40 m corresponding to infiltration velocities of 0.5-1 m/y. The correlation of measured discharges from subcatchment areas with those from the meteorological water balance proved deficits and surplus corresponding to mainly areas of recharge in the north-western part and discharge in the south-eastern one and indicate the direction of karst water flow under the phyllites from NW to SE along the dikes.